Intercultural Interpretation of Scripture: Evaluating the Approach of Jean-Claude Loba-Mkole for Interpreting the Bible in Africa - Aryeh, Daniel Nii Aboagye (Scriptura, 2024)
Intercultural methods of biblical interpretation are gradually gaining popularity and are preferred for biblical studies in the African context. Appropriate methods or approaches for biblical interpretation are critical if the objective of the interpretation is to engage the receptors’ or the target audience’s cultural features and that of the text for a mutual understanding of cultural values in a text to shape contemporary cultural issues. Intercultural criticism of scripture has been variedly engaged by biblical scholars for the interpretation of biblical passages. In this study, I explore the proposition of intercultural mediation by Jean-Claude Loba-Mkole and how he employed it to interpret scripture for the benefit of Africans. It emphasises the uniqueness and the weakness of the approach modelled by Loba-Mkole towards intercultural mediations and motivate others to consider intercultural mediation for biblical studies.